The Gift of God: The Deuteronomic Theology of the Land - Miller, Patrick D. (Interpretation, 1969)
The interrelation of God, land, and people in Deuteronomy has significance beyond the time of its own proclamation. The church hears here an affirmation of man's contemporary desire for land and home, a place where he can live to the fullest of his potential.